Patterns of offending: behavioral health and criminogenic influences - Guston, Kaitlin Alyssa (2018)
Due to the higher arrest and recidivism rates of offenders with behavioral health conditions (BHCs), it is often assumed that BHCs are a direct risk factor for engaging in criminal behavior. This assumption, however, has been proven incorrect by numerous studies. As a result, predicting recidivism for offenders with BHCs would be best achieved through the examination of general risk factors, clinical factors, and patterns of offending. Most contemporary risk assessments consider BHCs in their models by examining clinical risk factors, such as diagnoses or symptoms of conditions. Unfortunately, the poor definition of BHCs by most risk assessments negatively impacts their predictive accuracy and represents a caveat to their overall effectiveness. To negate this weakness, the current study seeks to validate the Comprehensive Addiction and Psychological Assessment – 5 (CAAPE – 5), as both a diagnostic and risk assessment for offenders with BHCs by examining the associations between specific BHCs and types of offending